2011
DOI: 10.5755/j01.sal.0.18.420
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ Attitudes Towards the Use of Blended Learning in General English Classroom

Abstract: The paper deals with the application of ICT and the use of blended teaching and learning within the curriculum of general English at the levels A1-B2 in tertiary education. The research presented in the paper focuses on analyzing the language teachers' experience in computer assisted language teaching as well as their practices and attitudes towards the blended learning courses created at the Centre of Foreign Languages at Vytautas Magnus University (VMU). Given the fact that the contemporary society is especi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 3 publications
1
15
0
Order By: Relevance
“…Technology gives learners a platform to practice their writing abilities and receive expert guidance. As opposed to other methods such as task-based learning that concentrate on oral practice alone, blended learning enhances writing skills, reading, and speaking, which are all fundamental to increasing English comprehension and communication (Bijeikiene, Rasinskiene, & Zutkiens, 2011). It is evident that the key advantage of blended learning is that both face-to-face and technology teaching methods support each other, and address the inadequacies found in either approach alone, so as to achieve the best results in language teaching.…”
Section: Blended Learning and Language Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…Technology gives learners a platform to practice their writing abilities and receive expert guidance. As opposed to other methods such as task-based learning that concentrate on oral practice alone, blended learning enhances writing skills, reading, and speaking, which are all fundamental to increasing English comprehension and communication (Bijeikiene, Rasinskiene, & Zutkiens, 2011). It is evident that the key advantage of blended learning is that both face-to-face and technology teaching methods support each other, and address the inadequacies found in either approach alone, so as to achieve the best results in language teaching.…”
Section: Blended Learning and Language Learningmentioning
confidence: 99%
“…Shea (2007) mentioned earlier that pedagogical richness transforms learning from mere presentation to active learning. Blended learning helps learners initiate, discover, and accomplish the procedurals of knowledge construction in the classroom set-up (Bijeikiene, Rasinskiene, &Zutkiens, 2011). This implies that learners can stimulate their cognitive abilities to create knowledge that has positive outcome in relation to what they are learning.…”
Section: Blended Learning and Language Learningmentioning
confidence: 99%
“…Even though, in language-teaching contexts, a plethora of studies have examined students' attitudes towards online EFL instruction (Aydin 2007;Chenoweth and Murday 2003;Chou 2010;Isman and Dabaj 2004;Scida and Saury 2006;Yang 2001), limited research has been conducted on teachers' perceptions of online language instruction (e.g., Bijeikienė, Rašinskienė, and Zutkienė 2011;Hampel and Hauck 2004;Murday, Ushida, and Chenoweth 2008;Shin and Son 2007). Based on the findings of the relevant literature, it can be concluded that the majority of language teachers adopt positive attitudes towards online instruction.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Online instruction would offer a plethora of benefits and merits for various educational stakeholders. The benefits of online instruction include the opportunity for ubiquitous learning, convenience, cost-effectiveness, provision of educational opportunities for learners and instructors, accessibility, learner-centredness and improvement of students' higher order thinking (Bijeikienė, Rašinskienė, and Zutkienė 2011;Britt 2006;Hill 2002;Hofmann 2002;Kim and Bonk 2006;Petrides 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Different teachers may blend different parts of their teaching with technology. To maximize the blended learning in English Language classroom, teachers need to understand why they apply blended learning and what are the tools used by English teachers in blended learning (Bijeikiene et al, 2011;Elliot, 2009;Motteram & Leithner, 2009). The tools used by English teachers in blended learning may help English teachers plan their blended learning lessons (Baltaci-Goktalay, 2010; Motteram & Leithner, 2009).…”
Section: Introductionmentioning
confidence: 99%